The Role of Street-level Bureaucracy in Licensing Services for Coal Mining Management in South Kalimantan - Anwar, Roy Rizali; Suaedi, Falih; Nugroho, Kris (Jurnal Manajemen Pelayanan Publik, 2024)
After the regulation on mineral and coal mining was appointed in 2020, the study attempts to ascertain the function of street-level bureaucracy in mining company license services. Qualitative research is the methodology employed. The findings of the study indicate that the enactment of regulation number 3 of 2020 has blunted the role of street-level bureaucracy in the implementation of mining policies due to the Provincial Government's loss of authority over the management of mining licensing governance in South Kalimantan. This implication also has an impact on mining activities without carrying out reclamation activities resulting in pollution of public waters. The impact of mining also the social aspects of society as a result of mining business permit holders' disobedience in implementing community development and empowerment programs. Coordination between regional sectors regarding coal mining activities in mining permit granting services must be strengthened. This is essential since it allows the Regional Medium-Term Development Plan and Regional Long-Term Development Plan to be implemented while integrating strategic development strategies for coal and metal mining.